Biomechanical investigations on compression, expansion, and flexion of tubal occluders: a finite element analysis - Song, Quan; Zhang, Zhuo; Tian, Xiaobao; Chen, Yu; Gao, Fei; Li, Zhongyou; Liu, Lingjun; Wang, Xiaoyan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundHydrosalpinx significantly reduces the success rate of embryo implantation no dedicated occlusion currently exists for its treatment. This study introduces a novel shape-memory-based Fallopian tube occluder and systematically evaluates its mechanical performance across designs with varying wire densities.MethodsThe proposed occluder features a mesh-based support structure with a symmetrical double-coil configuration, designed to enhance friction and reduce the risk of migration. Three geometric models were developed based on wire density (n): sparse (n = 84), standard (n = 113), and dense (n = 226). Finite element simulations were conducted to assess the mechanical response of each design during crimping, deployment, and bending.ResultsIn the sparse model, low filament density resulted in incomplete contact with the crimping tool, producing localized stress concentrations at the support and central regions with a maximum strain of 1.88%. The standard model demonstrated improved stress redistribution toward the connection zones and achieved a peak strain of 2.73%, providing reliable radial support while maintaining moderate compliance. The dense model, although free of dominant high-stress regions, exhibited severe localized stress (up to 1569.04 MPa) and a maximum strain of 12.73%, exceeding the superelastic recovery limit of the NiTi alloy. All three designs showed minimal axial shortening and radial recoil (<3%) after deployment, indicating limited post-deployment deformation. Load–displacement analysis revealed that increasing filament density led to higher bending stiffness and reduced flexibility.ConclusionThe sparse occluder offers high flexibility but lacks adequate structural support. In contrast, the dense design suffers from excessive deformation under compression, potentially compromising structural stability. The standard configuration provides an optimal balance between flexibility and support, making it the most promising candidate for clinical application.